Association of PTPN22 Haplotypes (−1123G>C/+1858C>T) with Rheumatoid Arthritis in Western Mexican Population - Yeniley Ruiz-Noa; Jorge Ramón Padilla-Gutiérrez; Jorge Hernández-Bello; Claudia Azucena Palafox-Sánchez; Yeminia Valle; Edith Oregón-Romero; Ana Laura Pereira-Suárez; Ana Guilaisne Bernard-Medina; José Francisco Muñoz-Valle (International Journal of Genomics)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by the presence of antibodies against cyclic citrullinated peptide (anti-CCP), a consequence of the breakdown of immune tolerance. The lymphoid tyrosine phosphatase (Lyp) protein has significant effects on maintenance of peripheral immune tolerance. Two polymorphic variants (−1123G>C and +1858C>T) at PTPN22 gene that encodes this protein have been associated with autoimmune disorders and found in strong linkage disequilibrium in Caucasian population. We evaluated whether PTPN22 haplotypes (−1123G>C/+1858C>T) are associated with anti-CCP antibodies, as well as susceptibility to RA in a Western Mexican population. A total of 315 RA patients and 315 control subjects (CS) were included. The polymorphisms were genotyped by PCR-RFLP and the anti-CCP antibodies were determined by ELISA. The PTPN22 polymorphisms were in strong linkage disequilibrium (D′ = 1.00 in CS). The susceptibility haplotype CT was significantly more frequent in RA patients than in CS (OR 2.18, 95% CI 1.15–4.16, p=0.01). No association between haplotypes and anti-CCP antibodies levels was observed. In conclusion, this study confirmed that −1123G>C and +1858C>T PTPN22 polymorphisms are in strong linkage disequilibrium and the CT haplotype is a susceptibility marker to RA in Western Mexico. However, the PTPN22 haplotypes are not associated with anti-CCP antibodies.